2008
DOI: 10.1364/ao.47.00h182
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval of the optical depth using an all-sky CCD camera

Abstract: A new method is presented for retrieval of the aerosol and cloud optical depth using a CCD camera equipped with a fish-eye lens (all-sky imager system). In a first step, the proposed method retrieves the spectral radiance from sky images acquired by the all-sky imager system using a linear pseudoinverse algorithm. Then, the aerosol or cloud optical depth at 500 nm is obtained as that which minimizes the residuals between the zenith spectral radiance retrieved from the sky images and that estimated by the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Several scientific efforts around the world to retrieve atmospheric aerosol-related properties from images taken from digital cameras and paintings [21] have returned promising results so far. Previous employments of similar methods, i.e., using digital cameras, have shown that the comparison of AOD derived from sky images with those retrieved with sunphotometers operated side by side showed differences similar to the nominal error claimed in the AOD sunphotometer networks [23]. A relevant field experiment showed that AOD from sky images is highly correlated with AOD from sunphotometers, with a correlation coefficient of 0.95 and an average retrieval error of around 7% [24].…”
Section: Estimation Of Air Quality From User-generated Sky Photosmentioning
confidence: 66%
“…Several scientific efforts around the world to retrieve atmospheric aerosol-related properties from images taken from digital cameras and paintings [21] have returned promising results so far. Previous employments of similar methods, i.e., using digital cameras, have shown that the comparison of AOD derived from sky images with those retrieved with sunphotometers operated side by side showed differences similar to the nominal error claimed in the AOD sunphotometer networks [23]. A relevant field experiment showed that AOD from sky images is highly correlated with AOD from sunphotometers, with a correlation coefficient of 0.95 and an average retrieval error of around 7% [24].…”
Section: Estimation Of Air Quality From User-generated Sky Photosmentioning
confidence: 66%
“…The all-sky imager was developed by the Atmospheric Physics Group at the University of Granada (GFAT) to provide images of the whole sky dome during the daytime for cloud and aerosol characterization (Cazorla et al, 2008a,b;Olmo et al, 2008). The all-sky imager registers full color images at three channels using a fish-eye lens: one is centered in red, another in green and the last one in blue.…”
Section: All-sky Imager and Raman Lidar Systemmentioning
confidence: 99%
“…Olmo et al (2008), the retrieval of optical depth using a CCD camera was studied, using the same system as A. Cazorla et al (2007).…”
Section: Cloudiness Indexesmentioning
confidence: 99%